Application of Information Digitalization Technology in Audit Process Through Intelligent Process Automation (IPA) Approach - Heriningsih, Sucahyo; Astuti, Sri; Marita, Marita (RSF Conference Series: Business, Management and Social Sciences, 2021)
Intelligent Process Automation (IPA) is a technology capable of organizing automation processes for structured, semi-structured, and unstructured data. In audit assignments, there are three types of assignments, namely structured, semi-structured and unstructured assignments. This study aims to identify the possibility of applying IPA (Intelligent Process Automation) in audit assignments. By using IPA technology, it is expected to be able to create efficiency and effectiveness in the audit process. As we know that audit assignments require time and high costs, so IPA technology is expected to be able to shorten audit time and costs without reducing the quality of services provided by auditors. This research is qualitative research using primary data. The respondents in this study are public accountants who work in the Public Accounting Firm (KAP). The research instrument consists of mapping structured, semi-structured, unstructured audit assignments; then identified each with the possibility of applying IPA (Intelligent Process Automation) in each audit process. Respondents in this study were forty-one. The results of the analysis using descriptive analysis and frequency analysis, and it was found that the use of automation of audit procedures at the audit planning stage was still rarely used. With the following details (1) structured assignment, still rarely used; (2) semi-structured assignment, still rarely used; (3) unstructured assignments, sometimes used. Meanwhile, the use of automation of audit procedures at the control and substantive testing stage as well as the overall conclusion (audit completion) stage is sometimes used, both structured, semi-structured, and unstructured assignments.